SECURE DATA GROUP SHARING AND CONDITIONAL DISSEMINATION WITH MULTI OWNER (International Journal of Food and Nutritional Sciences, 2024)
In contemporary data management paradigms, ensuring secure data sharing while maintaining control over dissemination conditions is a crucial challenge. This paper proposes a novel framework for secure data group sharing and conditional dissemination with multi-owner capabilities. The framework addresses the complexities of collaborative environments where multiple entities have ownership rights over the shared data. Leveraging cryptographic techniques and access control mechanisms, our approach provides a robust solution for securely sharing data among authorized users while allowing owners to specify conditional access policies. These policies enable owners to dictate access rights based on predefined conditions such as time, location, or user attributes. We present a detailed architecture and algorithms for implementing the proposed framework, along with a comprehensive security analysis to demonstrate its effectiveness in safeguarding data confidentiality and integrity. Through experimental evaluations, we validate the performance and scalability of our solution, highlighting its suitability for real-world applications in collaborative environments where secure data sharing and conditional dissemination are paramount concerns.